2020
DOI: 10.14712/23366486.2020.1
|View full text |Cite
|
Sign up to set email alerts
|

Miera starostlivosti o seba, vnímaného stresu a celkovej pracovnej spokojnosti, ako aj vzťahy medzi nimi u pomáhajúcich pracovníkov poskytujúcich sociálne služby

Abstract: Vykonávanie pomáhajúcej profesie sa spája aj s vysokým prežívaním stresu. Cieľom tejto štúdie je porovnaťreprezentatívnu vzorku slovenských pomáhajúcich profesionálov poskytujúcich sociálne služby (N = 729) s americkými normami v porovnateľných skupinách. Slovenská a americká vzorka sa významne nelíšili v miere prežívaného stresu, ktorá bola posudzovaná Škálou vnímaného stresu (Cohen, Kamarck, Mermelstein, 1983), avšak celková sumarizovaná pracovná spokojnosť ktorá bola posudzovaná Dotazníkom pracovnej spokojn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…There are many programs aiming at increasing self-care nowadays (e.g. Mesárošová et al, 2019), yet, it seems that self-care is not a core issue for all participants. For the studied risk-group of professionals, there may be strategies that are more suitable and effective in alleviating the depressive symptoms and maintaining good health, such as supporting recreation, leisure and hobby activities.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are many programs aiming at increasing self-care nowadays (e.g. Mesárošová et al, 2019), yet, it seems that self-care is not a core issue for all participants. For the studied risk-group of professionals, there may be strategies that are more suitable and effective in alleviating the depressive symptoms and maintaining good health, such as supporting recreation, leisure and hobby activities.…”
Section: Discussionmentioning
confidence: 99%
“…The growing levels of perceived stress are not localized plausibly only in the USA. The stress levels in selected professions, which are potentially prone to stress, have been assessed also in Slovak settings (Nezkusilová, Hricová, & Mesárošová, 2019). The results revealed that in large representative sample of 729 individuals working in professions prone to burnout, perceived stress was relatively high in average, yet not significantly different to the stress levels of the employed workers in the USA (Nezkusilová et al, 2019) based on the results of perceived stress from the year 2009 (Cohen & Janicki-Deverts, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation